Differential Regulation of ftsZ Transcription during Septation of Streptomyces griseus - Kwak, Jangyul (American Society for Microbiology, 2001)
Streptomyces has been known to form two types of septa. The data in this research demonstrated that Streptomyces griseus forms another type of septum near the base of sporogenic hyphae (basal septum). To understand the regulation of the septation machinery in S. griseus, we investigated the expression of the ftsZ gene. S1 nuclease protection assays revealed that four ftsZ transcripts were differentially expressed during morphological differentiation. The vegetative transcript (emanating from P(veg)) is present at a moderate level during vegetative growth, but is switched off within the first 2 h of sporulation. Two sporulation-specific transcripts predominantly accumulated, and the levels increased by approximately fivefold together shortly before sporulation septa begin to form. Consistently, the sporulation-specific transcripts were expressed much earlier and more abundantly in a group of nonsporulating mutants that form their sporulation septa prematurely. Promoter-probe studies with two different reporter systems confirmed the activities of the putative promoters identified from the 5′ end point of the transcripts. The levels and expression timing of promoter activities were consistent with the results of nuclease protection assays. The aseptate phenotype of the P(spo) mutant indicated that the increased transcription from P(spo) is required for sporulation septation, but not for vegetative or basal septum formation.